Dietrich Bonhoeffers "religionslose" Evangelisation: Formate seiner ökumenischen Spiritualität und die Oxfordgruppenbewegung - Reller, Jobst (Communio viatorum, 2023)
Dietrich Bonhoeffer (1906-1945), made a martyr by the Nazi German regime in 1945, is still widely read because of his ideas: the proclamation of Christian faith in a non-religious comprehen-sive worldly way, a Bible oriented spirituality of silence, confession with a political horizon. In Norwegian sources the profile of the US based Oxford Group Movement, founded by the Lutheran pastor Frank Buchman (1878-1961; later: Moral Rearmament, today: Initiatives of Change) has been identified as an influential revival movement appe-aling to political elites in Europe in the 1930’s. The article tries to show to which extent Bonhoeffer may have shaped his ideas on preaching and spirituality in confrontation with Buchman’s movement. The Nor-wegian author Ronald Fangen (1895-1946) plays a substantial role for the profile of the Oxford Group Movement in Norway.